Observer‐based adaptive sliding mode control of uncertain switched systems. Issue 3 (1st February 2020) - Lin, Luxin; Liu, Zhen; Kao, Yonggui; Xu, Ruiping
Abstract : In this study, an observer‐based adaptive sliding mode control scheme is proposed for a class of uncertain switched systems. A state observer is utilised to estimate the unmeasured state variables, from which a novel sliding surface is provided. Based on linear matrix inequality technique, Lyapunov stability theory and the average dwell time approach, exponential stability of the overall closed‐loop switched system is guaranteed by virtue of the proposed control scheme. An adaptive reaching motion control law is then developed to ensure the state trajectory can be driven onto the predesigned sliding surface in finite time. At last, the validity of the proposed method is demonstrated by simulation results.